The 'full-blown' MRI of sudden hearing loss: 3D FLAIR in a patient with bilateral metastases in the internal auditory canals. Issue 1 (February 2018) - Conte, Giorgio; Di Berardino, Federica; Zanetti, Diego; Avignone, Sabrina; Sina, Clara; Iofrida, Elisabetta; Triulzi, Fabio
We report a case of a 57-year-old man with bilateral masses in the internal auditory canal. The peculiar findings at magnetic resonance imaging with tridimensional fluid-attenuated inversion recovery sequence combined with clinical data provided new insights into understanding the pathophysiology of the hearing loss.